PENGARUH ALARM MINUM OBAT (AMINO) UNTUK MENINGKATKAN KEPATUHAN MINUM OBAT PASIEN HIPERTENSI - Yusmaniar Yusmaniar; Yugo Susanto; Surahman Surahman; Riza Alfian (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2020)
According to data from Riskesdas 2018 there was an increase in the prevalence of hypertension in Indonesia from 25.8% in 2013 to 34.1% in 2018. Inadequacy in taking medicine is one of the factor contributed. This research discusses the importance of the application of taking medication alarms for consultation taking medication and hypertension patients' blood pressure. The study was conducted using a quasi-experimental two group pretest posttest design. Observed data are the level of adherence and blood pressure. The study was conducted at 2 Banjarmasin Puskesmas. Data collection collected in the period August - October 2019. Research data were obtained by filling in the MARS questionnaire, while blood pressure data was taken from medical records. This study involved 25 samples each in the control and intervention groups. The intervention given was in the form of installing medication alarm in sample smartphone. The Wilcoxon Test to determine differences in the average category of level of adherence, and blood pressure samples at the beginning and end of the study. In the pre study 100% of the sample intervention group were at moderate medication adherence rates and in the post study it changed to 40% at moderate medication adherence levels and 60% at high medication adherence levels. Statistical test results show a significant increase in medication adherence. Systolic and diastolic blood pressure in the intervention group also experienced a significant decrease (p <0.05). The results of the study in the control group showed no increase in medication adherence and no significant decrease in blood pressure.